Mujeres tras la huella de los soldados - Larraín Mira, Paz (Historia, 2000)
Women took part in the War of the Pacific in more than one way" Some were "cantineras"; others stayed at home but helped according to their possibilities, and finally there were the camp followers, which are te object of this study. Most of them followed their husbands or friends, but there were also single women who simply wished to go to the battlefront and embarked in large numbers together with the troops. However, the problems created by so many females in the camps became evident after a few months, and the Governmentt issued several decreed forbidding women to travel in military transports. These orders were repeatedly flaunted with the help of the soldiers who even lent them their spare uniforms as a disguise. This explains the great number of women who returned together with the Chilean army in 1884, at the end of the war.